Dinamika Konflik Agraria di Desa Alastlogo Kabupaten Pasuruan, 1960-2024 - Lailatul Fitriyah (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
Indonesia, as an agrarian country, faces various problems in the agricultural sector. Agrarian conflicts still frequently occur in many areas, including inAlastlogo Village, Pasuruan Regency. This article aims toprovide a historical review of the land conflict that occurred in Alastlogo Village, Pasuruan Regency, focusing on the general description of the Alastlogo Village community, the conflict in Alastlogo Village, Pasuruan RegencyPasuruan from 1960 to 2024, and the impact ofagrarianconflict in Alastlogo Village. This article uses a historical method with fivesteps, namely topic selection, heuristics, verification, interpretation, andhistoriography. The results of the researchshow that the agrarian conflict in Alastlogo Village is a prolonged conflict thathas been going on since 1960 between the Indonesian Navy (TNI AL) and the farming community. The conflicthas caused suffering for the community, especially in 2007, whichbecame a historic tragedy when violence committed by the TNI ALcaused four people to die and eight to be injured. Despite various attempts at resolution, the agrarian conflict in Alastlogo Village has yet to be fully resolved. This situation continues to have asignificant impact on the social and economic relations of the local community.